PELAKSANAAN KEWAJIBAN PELAPORAN ANNUAL DAN BIENNIAL (IMPLEMENTATION) REPORT CONVENTION ON INTERNATIONAL TRADE OF ENDANGERED SPECIES (CITES) 1973 DI INDONESIA - Damayanti, Alfina; Sagio, Ibrahim; Arsensius, Arsensius (Tanjungpura Legal Review, 2023)
Abstract  Convention On International Trade of Endangered Species (CITES) 1973 as an international treaty aimed at protecting flora and fauna from extinction due to international trade makes a mechanism of control of international trade in species of flora and fauna.  To support the implementation of this trade control system, the state is required to collect reports known as the Annual Report and Biennial (Implementation) Report.  Indonesia, as a member state of CITES, has the obligation to carry out such reporting in accordance with existing regulations. This study aims to identify and analyse the implementation of CITES reporting obligations in Indonesia, especially related to the Annual Report and Biennial (Implementation) Report. These reports play an important role in monitoring Indonesia's compliance with CITE provisions. The research method used is data collection through literature study, document analysis, and policy analysis related to CITES Annual and Biennial (Implementation) Report reporting. The collected data will be analysed to see the extent of Indonesia's compliance in carrying out reporting obligations and what obstacles are faced by Indonesia in its implementation. The results of this study are expected to provide a better understanding of the implementation of CITES reporting obligations in Indonesia. In addition, this research is also expected to provide recommendations and inputs for the government and relevant stakeholders to improve the quality and compliance with reporting obligations as a commitment to protect endangered wildlife through the implementation of CITES.  Abstrak  Convention On International Trade Of Endangered Species (CITES) 1973 sebagai perjanjian internasional yang bertujuan untuk melindungi flora dan fauna dari kepunahan akibat perdagangan internasional membuat suatu mekanisme kontrol perdagangan internasional spesies flora dan fauna. Untuk mendukung terlaksananya sistem kontrol perdagangan ini maka negara diwajibkan untuk mengumpulkan laporan yang dikenal dengan Annual Report dan Biennial (Implementation) Report. Indonesia, sebagai negara pihak anggota CITES memiliki kewajiban melaksanakan pelaporan tersebut sesuai dengan ketentuan yang ada. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis pelaksanaan kewajiban pelaporan CITES di Indonesia, terutama terkait Annual Report dan Biennial (Implementation) Report.. Laporan-laporan ini memiliki peran penting dalam memantau kepatuhan Indonesia terhadap ketentuan CITE. Metode penelitian yang digunakan adalah pengumpulan data melalui studi pustaka, analisis dokumen, dan analisis kebijakan terkait pelaporan Annual dan Biennial (Implementation) Report CITES. Data yang terkumpul akan dianalisis untuk melihat sejauh mana kepatuhan Indonesia dalam melaksanakan kewajiban pelaporan dan kendala apa saja yang dihadapi oleh Indonesia dalam pelaksanaannya. Hasil penelitian ini diharapkan dapat memberikan pemahaman yang lebih baik tentang pelaksanaan kewajiban pelaporan CITES di Indonesia. Selain itu, penelitian ini juga diharapkan dapat memberikan rekomendasi dan masukan bagi pemerintah dan pemangku kepentingan terkait untuk meningkatkan kualitas dan kepatuhan terhadap kewajiban pelaporan sebagai komitmen perlindungan terhadap satwa liar terancam punah melalui implementasi CITES.